2006
DOI: 10.1515/cclm.2006.110
|View full text |Cite
|
Sign up to set email alerts
|

Serum homocysteine levels and paraoxonase 1 activity in preschool aged children in Greece

Abstract: The significant percentage of elevated tHcy levels observed in healthy preschool cases and the negative tHcy correlation with PON1 activity are reported for the first time. Since children with a family history of cardiovascular disease have higher levels of serum Hcy, tHcy screening in children, even of this age, in relation to other parameters, such the protective PON1, might prove a useful prevention procedure for the genetic risk of premature atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
1
7
1
Order By: Relevance
“…In clinical investigations, serum PON activity has been reported to be negatively associated with the serum Hcy concentration (118,163,165,182,185). One study reported that the hydrolytic activity of human PON1 toward Hcythiolactone is associated with the PON1-192-Arg/Arg and PON1-55-Leu/Leu genotypes and strongly correlated with PON1's hydrolytic activity toward organophosphate paraoxon substrates (182).…”
Section: B Pons Protect Against Hcy Toxicitymentioning
confidence: 99%
“…In clinical investigations, serum PON activity has been reported to be negatively associated with the serum Hcy concentration (118,163,165,182,185). One study reported that the hydrolytic activity of human PON1 toward Hcythiolactone is associated with the PON1-192-Arg/Arg and PON1-55-Leu/Leu genotypes and strongly correlated with PON1's hydrolytic activity toward organophosphate paraoxon substrates (182).…”
Section: B Pons Protect Against Hcy Toxicitymentioning
confidence: 99%
“…Now an elevated plasma tHcy level is well recognized as an important vascular risk factor and atherosclerosis in the coronary, cerebrovascular and peripheral arterial circulation [6–9], even if the degree of hyperhomocysteinaemia is moderate. Among the determinants which predispose to premature thromboembolic and atherothrombotic events, serum activity of paraoxonase 1 (PON1), which is mainly synthesized in the liver [10], has been shown to be a predictor of cardiovascular disease [11,12] and to be negatively correlated with serum tHcy levels [13,14]. Moreover, PON1 is a thiolactonase, which hydrolyses homocysteine thiolactone to Hcy.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, preterm babies have 24% lower activities compared with term babies (Ecobichon and Stephens 1973), suggesting that PON1 levels in the fetus may be even lower. A few studies have measured PON1 activities in healthy young children at single points in time (Garces et al 2008; Karikas et al 2006; Sumegova et al 2007; Vincent-Viry et al 2003), but only one study has described the ontogenetic profile of PON1 activity in the same individuals over time. This study (Cole et al 2003) of nine children demonstrated high inter-individual variation of PON1 from birth to 2 years of age; PON1 activities increased over time and reached a plateau between 6 months and 2 years of age in most, but not all, individuals.…”
mentioning
confidence: 99%